PELAKSANAAN METODE MURAJA’AH HAFALAN AL- QUR’AN DI MADRASAH TSNAWIYAH AL–MUNAWWARAH KOTA JAMBI - Suryani, Lily; Mahmud MY (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis discusses the implementation of the muraja’ah method in memorizing the Qur’an at Madrasah Tsanawiyah Al-Munawwarah. The problem addressed in this research is how the muraja’ah method is implemented in Qur’an memorization and how the results of its implementation contribute to students’ memorization achievement. This study employed a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data display, and data verification.The results of the study indicate that the implementation of the muraja’ah method in Qur’an memorization at Madrasah Tsanawiyah Al-Munawwarah includes four forms of practice: Collective muraja’ah recitation supervised by the tahfidz teacher; Peer muraja’ah conducted three times a week (approximately 43%);Muraja’ah of both old and new memorization submitted to the tahfidz teacher;Qur’an memorization examinations. The results show that students successfully achieved the memorization targets set by the school, namely memorizing Juz 29 and Juz 30. Students were able to recite the Qur’an with proper makhraj (pronunciation) and tajwid (rules of recitation). After the implementation of the muraja’ah method, students’ memorization became more fluent, tartil (measured and rhythmic), and eloquent. The implications of this study suggest that schools should provide adequate facilities and infrastructure as supporting factors for educational success and the achievement of learning objectives. Teachers are encouraged to actively motivate students, ensure their readiness and concentration, and consistently guide them in reviewing their memorization. Students are expected to be more active in improving their understanding of Qur’an memorization lessons and to develop greater confidence in participating in learning activities. Keywords : Implementation, Muraja’ah Method, Qur’an Memorization